Answer:
-10
Step-by-step explanation:
g(x) = -3x^2 +4x+5
Let x = 3
g(3) = -3*(3)^2 +4*3+5
= -3*9 +12+5
= -27+12+5
= -10
This is just me typing so that it’s 20 letters long
Answer:
$14
Step-by-step explanation:
What you would do is 84/6 considering the bike cost 6 times as much as the helmet. And you would get 14 so the helmet would cost $14. However to check it you can find what times 6 = 84 which 6 x 14 = 84.
Hope this helps!
Answer:
A
Step-by-step explanation:
Given :
2x + 4y = 14 ---------- eq 1
4x + y = 20 ---------- eq 2
if you multiply eq 2 by -4 on both sides, you get
-4 (4x + y = 20) = -4 (20)
-16x -4y = -80 --------- eq3
we can see that eq. 1 and eq 2 together forms the system of equations presented in option A, Hence A is equvalent to the orginal system of equations given in the question.